“All These Nouns Together Just Don’t Make Sense!”: An Investigation of EAP Students’ Challenges with Complex Noun Phrases in First-Year College-Level Textbooks - Priven, Dmitri (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2020)
Complex noun phrases (CNP) are a major vehicle of academic written discourse (Halliday, 1988; 2004). However, in spite of the view that they pose significant challenges to English language learners, they are often overlooked in preparatory English for Academic Purposes (EAP) programs. This mixed methods study aims to investigate to what extent CNP present syntactic parsing challenges for upper-level college EAP students, and whether there is a perceived need for direct instruction in CNP in EAP programs. A special CNP proficiency test was administered to 70 upper-level Ontario college EAP students and a native speaker comparator group, and the results were compared with those obtained from interviews with seven of the test-takers. The results obtained from the statistical analyses and the interviews indicate that CNP are challenging to parse for upper-level EAP students and that direct instruction in CNP may be beneficial for improving their reading comprehension. Some teaching implications of the findings are also addressed.